(untitled) (Fiep Bulletin - online, 2011)
There is a need to know the professionals engaged in hospital recreation if we want to perceive that playing games is also possible when one is sick, once enjoyment activities could contribute towards rehabilitating diseased children. The objective of this descriptive-exploratory study is to describe the characteristics needed by professionals engaged in Hospital Recreation, within the following subjects: psychological ( socio-affective, interpersonal relations), ethical, pedagogical, technical and intellective. An open-question questionnaire was applied to 18 subjects (14 females and 4 males), including doctors, physiotherapists, nurses, technicians, university professors and the psychologist at Hospital Santa Cruz, RS. Based on the results, we perceived that: a) with regard to the psychological characteristics, the following are of note: responsibility, dedication, kindness, initiative, emotional control, integrity, intellectual maturity, self-esteem, knowledge of subjectivity production; b) as to the pedagogical/technical/intellective characteristics, the following stand out: to master the knowledge of particularities related to a child’s development and growth process; possess didactic-methodological knowledge appropriate for the teaching-learning process of games, enjoyment activities, dance, music, the capacity to tell stories, use creativity, adjust the service to different situations in a recreational room and to bed-ridden children (individualized assistance); c) the major ethical characteristics were as follows: secrecy should be kept regarding the hospital report of the patient, family members, discretion, anonymity of the disease and symptoms. Therefore, we suggest that all characteristics inherent to hospital recreationists should be taken into account when it comes to developing qualification and upgrading curriculum programs for the healthcare professionals responsible for recreation activities in hospitals.